2006
DOI: 10.1002/pssb.200541395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dielectric screening on the binding energies and diamagnetic susceptibility of a donor in a quantum well wire

Abstract: The effect of the dielectric screening on donor binding energies in a quantum wire has been estimated. Since the screening function is shown to be significant in a few phenomena like carrier transport, and not so in a few cases like the donor binding energy calculations, five different screening functions have been used in the calculations to see their relative merits. It is observed that the dielectric function obtained by Resta using the Thomas -Fermi approximation not only gives lower estimates of the ioniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Experimental realization of impurity states of acceptor in optical spectra was first addressed by Miller et.al (2) . The effect of spatial variation of dielectric screening on donor in finite and infinite wire was reported by Latha et.al (3) . Similar study is made in infinite (4) and finite (5) Quantum well for both donor and acceptor.…”
Section: Introductionmentioning
confidence: 83%
“…Experimental realization of impurity states of acceptor in optical spectra was first addressed by Miller et.al (2) . The effect of spatial variation of dielectric screening on donor in finite and infinite wire was reported by Latha et.al (3) . Similar study is made in infinite (4) and finite (5) Quantum well for both donor and acceptor.…”
Section: Introductionmentioning
confidence: 83%
“…20 The effect of spatial dielectric screening on the diamagnetic susceptibility of a donor in low dimensional semiconducting systems like quantum well, quantum well wire and quantum dot in the infinite barrier model has been investigated by Nithiananthi et al 21 The effect of the dielectric screening on donor binding energies in a quantum wire has been estimated by Latha et al . with five different screening functions. 22 Keldysh has shown that in thin films, if the dielectric constant of the film is much larger than that of the substrate, as film thickness decreases, the Coulomb interaction increases strongly. 23 Shik, on the other hand, observed a decrease of conductivity with the film thickness, when screening in thin films is taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the results reported earlier show that the DSF increases the confinement and hence increases the binding energy for all wellwidths. 18,19,22 The reasons for this difference may be due to the asymmetric nature of the well, and the inclusion of the effect of image charges.…”
mentioning
confidence: 99%
“…Moreover, the improvements of spintronics require an extensive study of magnetic properties of low dimensional heterostructures. Also, diamagnetic susceptibility of a hydrogenic donor has been studied for a quantum well [4], and for a quantum dot [5]. In semiconductors with anisotropic carrier effective mass, hydrogenic donors are extended along the heavy mass.…”
Section: Introductionmentioning
confidence: 99%